2014 IEEE Healthcare Innovation Conference (HIC) 2014
DOI: 10.1109/hic.2014.7038926
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of a low-cost, handheld reader for diagnosing anemia in Blantyre, Malawi

Abstract: Anemia, a condition characterized by insufficient hemoglobin, affects 56.2% of pregnant women and 66.1% of children under five in low-resource countries. Though hemoglobin concentration measurement is the most common laboratory test in the world, the high cost of disposables (>$1.00 per test in Malawi) limits its availability in these settings. We have demonstrated a spectrophotometric method that reduces the per-test cost of anemia diagnosis to under $0.01 by using chromatography paper as the only disposable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…7,8 However, they may still be subjected to errors during the collection and chemical analysis of the samples. 9,10 In addition, the extraction of blood samples may bring some discomfort and, like any invasive procedure, can incur additional risks for a patient.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, they may still be subjected to errors during the collection and chemical analysis of the samples. 9,10 In addition, the extraction of blood samples may bring some discomfort and, like any invasive procedure, can incur additional risks for a patient.…”
Section: Introductionmentioning
confidence: 99%
“…1 E ). An algorithm described in Bond et al ( 17 ) was used to compute the optical density of the sample. Apertures made of black cardstock were placed along the optical pathway to reduce the amount of scattered light entering the sample detector.…”
Section: Methodsmentioning
confidence: 99%
“…Thirteen studies (32%) reported challenges to POC(Hb)T use [13,15,19,29,31,32,47,49,50,54,55,58,60]. Overestimation of Hb concentration (n = 5) and errors in sampling and environmental factors (n = 5) were the most frequently reported challenges.…”
Section: Challengesmentioning
confidence: 99%
“…Accuracy data were not extracted in three studies due to pooled data with adults and children (n = 2) and use of a non Hb-measuring tool (n = 1) [32,50,62]. Five studies reported accuracy results were clinically unacceptable (Table 2) [15,29,31,32,49]. Test performance varied across studies.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation